Objects of Worth, Objects of Desire: Toward A Dictionary of Traded Goods and Commodities, 1550-1800 - Cox, Nancy (Material Culture Review, 1994)
Obsolete specialist vocabularies of interest to economic and cultural historians are ill served by the major dictionaries, whose sources are largely literary and whose brief illustrative quotations are taken out of context. A project at the University of Wolverhampton, England, is attempting in part to rectify this deficiency by producing a specialized dictionary of com-modity terms, 1550-1800. This paper is con-cerned not with the project’s history, but with some of the issues that it needs to address. These are discussed within the framework of the three principles that underpin the project’s work: the use of a wide range of sources acces-sible between the word and the object. An appendix details the computing infrastructure and gives some examples of possible dictionary entries. Résumé Les termes spécialisés désuets qui intéressent les historiens de l’économie et de la culture ne figurent pas suffisamment dans les grands dic-tionnaires, dont les sources sont principale-ment littéraires et dont les brèves citations offertes en exemples sont prises hors contexte. Un projet de l’Université de Wolverhampton (Angleterre) vise à rectifier la situation en pro-duisant un glossaire des termes relatifs aux produits en usage entre 1550 et 1800. Cet ar-ticle ne fait pas l’historique du projet, mais aborde certaines questions à régler. Ces der-nières sont examinées en fonction de trois prin-cipes qui sous-tendent le projet : l’utilisation de nombreuses sources qui permettent de rattacher le mot et l’objet. Une annexe décrit en détail l’infrastructure informatique du projet et donne des exemples d’unités lexicales.